A case of mandibular peripheral osteoma on the inferior border of the mandible. Issue 3 (27th May 2020) - Kamimura, Ryouta; Fukumoto, Chonji; Hasegawa, Tomonori; Komiyama, Yuske; Fujita, Atsushi; Kawamata, Hitoshi
Abstract: Reactive bone growth is often clinically difficult to distinguish from true tumors, and both types of lesion are frequently lumped together as "osteomas." We carried out surgical resection of an osteoma on the inferior border of the mandible of a patient with no history of mechanical stimulus or trauma that showed autonomous growth over time on imaging assessments. We were therefore considered this lesion as a true tumor, and report this case with a discussion of the literature. It is important to resect lesions with a sufficient safety margin when the lesions were classified as "true osteomas" on the basis of appropriate diagnosis. If the lesion were finally diagnosed as tumors, careful follow‐up is required.